Four Men in Buick (Stearns History Museum, 235 S. 33rd Avenue, St Cloud, MN 56301; http://www.stearns-museum.org)
Lake Henry, August Hansen driving with Jacob Brick next to him, Archie Chisholm and Ben Schoener in back seat.
United States
Minnesota
Stearns
Lake Henry Township
Lake Henry, August Hansen driving with Jacob Brick next to him, Archie Chisholm and Ben Schoener in back seat.
Keywords: Lake Henry; Hansen, August; Brick, Jacob, 1857-1957; Chisholm, Archie; Schoener, Ben; Automobiles; Men; Clothing and dress; Hats; Wooden buildings; Dirt roads; Transportation